The Social Services : The immediate problem and the way forward (London : The Socialist Medical Assocation)
1944 1944 1940s 34 pages promote social activities and education for their members. Progressive councillors often spend much of their time running one-man (or one-woman) advice bureaux for their constituents on all social problems. Tenants and Residents' Associations have gone far beyond defending the economic interests of their members, and become the social centres of their neighbourhoods. Organisations such as Unity Theatre show the potential resources available for developing cultural activities, and the scope for co-operation between voluntary and professional workers. As more and more of our political objectives are gained, workers in the Labour Movement will be able to spend more time on developing the social services, and many more will be drawn into activity as the political consciousness of the people grows. Voluntary workers of this kind will not rally to the old type of voluntary organisations (which they regard, with some justification, as "charity"), but will readily support services which they have asked for, and which they feel to be their own by right, and not given to them by benevolent outsiders. 12. Industrial Problems The worker has needs and desires as a private citizen, or as a consumer, which the projects we have outlined above are intended to fulfil at least in part. But it is also necessary to consider the 24 15X/2/464/1